Influence of porosity and aspect ratio of nanoparticles on the interface modification of glass/epoxy composites. Issue 9 (23rd February 2017) - Najafi, Hamideh; Zadhoush, Ali; Talebi, Zahra; Rezazadeh Tehrani, Sayed Pedram
Abstract : Various nanostructured particles including colloidal silica nanoparticles, mesoporous silica aerogel, silicon carbide nanoparticles, and nanowhiskers were used to modify the glass fibers surface. The influence of porosity and aspect ratio of nanoscale particles on the mechanical properties of modified glass fiber/epoxy composite samples were investigated. Fiber surfaces treated with nanoscale particles exhibited much higher coefficient of friction and roughness than unmodified fiber surfaces. Surface modified composites by silica aerogel showed the maximum increase in interfacial shear strength (IFSS) by 31%. An increase of 61% in shear punch stress was obtained by samples treated with silica aerogel and 27% for samples treated with silica nanoparticles. Improvement of 23% and 63% in tensile and flexural strength of composite samples treated with 0.5 wt% of SiC nanowhiskers and 7% and 18% for samples treated with the same content of SiC nanoparticles were observed. POLYM. COMPOS., 39:3073–3080, 2018. © 2017 Society of Plastics Engineers